(untitled) (Ozone Therapy Global Journal, 2019)
One of the techniques used to transfer ozone to a patient consists of bubbling ozone at low concentrations in a saline solution and then, injecting the saline solution into the patient. Next, it is analyzed the efficiency of the indicated technique, in terms of the ozone dose that has been finally transferred to the patient via intravenous. For this study, we have proceeded to bubble ozone at different standardized concentrations (1013.25 hPa and 273.15 K, id est, 1 atm and 0ºC) in a container with saline solution and then, we make the saline solution to pass through an ozone concentration analyzer in liquids, that will indicate the ozone retained in the saline solution. This amount of dissolved ozone was also compared with the amount of ozone dissolved in distilled and deionized water, under the same conditions. After 10 minutes of ozone bubbling, a quarter of the programmed concentration (25%) remained in the liquid (approximately), which confirmed the recommendations of the ISCO3 [1]. This way, the user can know in advance the dose that will be applied to the patient by using this technique.